PRAKTIK PENDIDIKAN MORAL EMILE DURKHEIM DALAM KOMUNITAS SOLO MENGAJAR - Okta Hadi Nurcahyono; Aldestina Putri Sarwastuti; Abdul Rahman (Sosio-Didaktika: Social Science Education Journal, 2020)
Moral education is a way to instill good behavior ini a person so that we can became a good person and be accepted in social life. Through a community, moral education can be cultivated in a person and of course in the development of child. The purpose of this study was to determine the practice of moral education (Emile Durkheim) in a Solo Mengajar community. This research uses qualitative research with a qualitative descriptive approach. Research data collection techniques include observation, interviews and documentation. Resource persons in this study were volunteers and students of Solo Mengajar. The results of this study describe the elements of Emile Durkheim’s moral education, the spirit of dicipline, the bond between groups and autonomy of self determination (will) in the Solo Mengajar Community. The spirit of dicipline in this community is seen from the teaching process and the rules that are applied when teaching takes place. The bond between gruops in the Solo Mengajar community begins with building bonds between volunteers through the meetings that are held. By uniting the closeness between these volunteers which then made it easier for them to carry out vatious varied activities to tie the children in the teaching environment. Meanwhile, the volunteers’ understanding of the characteristics of children and their surroundings as well as the problems that occur during the teaching process is self-determination or the will this community. So they can determine what actions or activities they will do at teaching time.Keywords : Community, Moral Education, Solo Mengajar